An Analysis of Bidding Strategy, Project Performance and Company Performance Relationship in Construction. (2015) - Wibowo, Mohamad Agung; Astana, I. Nyoman Yudha; Rusdi H.A.,
Abstract: Company performance defined as a whole achievement of the company during certain periods affected by the operations in utilizing all company resources[1] . While project performance is the record of outcomes produced or services on a specified job function or activity during a specified time period. Department of the Environment Transport and Regions (DETR), (2000) in[2] explain that project performance have been aggregated to evaluate the organization performance. In the other words company performance determine by sum of some project performance. Generally the project success obtained from a good process by using a right strategy. Bidding strategy is one of the important strategies in the early stages of project life cycle to determine project success. Bidding strategy is a management skills of using all available resources related, in order to offer a comprehensive and competitive bidding through consider various aspects, including internal, external and environment, with aim to win the bidding competition, and provide maximum project performance[3] . The study aims to analysis the influence of bidding strategy on project performance and company performance and to identify the most decisive factor of each variable. Data were collected from questionnaire survey and interviews of 61 major contractors in four major cities in Indonesia. The analysis used is Structural Equation Modeling Partial Least Squares (SEM PLS) with SmartPLS 2.0.M3. The finding indicate that bidding strategies had a direct impact on project performance, but indirect impact on company performance, while project performance becomes a mediation variable of bidding strategy and company performance relationship.